Chronic Binge Alcohol Administration Increases Intestinal T‐Cell Proliferation and Turnover in Rhesus Macaques. (4th July 2015) - Veazey, Ronald S.; Amedee, Angela; Wang, Xiaolei; Bernice Kaack, M.; Porretta, Constance; Dufour, Jason; Welsh, David; Happel, Kyle; Pahar, Bapi; Molina, Patricia E.; Nelson, Steve; Bagby, Gregory J.
<x xml:space="preserve">Abstract</x> Background Alcohol use results in changes in intestinal epithelial cell turnover and microbial translocation, yet less is known about the consequences on intestinal lymphocytes in the gut. Here, we compared T‐cell subsets in the intestine of macaques before and after 3 months of chronic alcohol administration to examine the effects of alcohol on intestinal T‐cell subsets. Methods Rhesus macaques received either alcohol or isocaloric sucrose as a control treatment daily over a 3‐month period via indwelling gastric catheters. Intestinal lymphocyte subsets were identified in biopsy samples by flow cytometry. Twenty‐four hours prior to sampling, animals were inoculated with bromo‐deoxyuridine (BrdU) to assess lymphocyte proliferation. Immunohistochemistry was performed on tissue samples to quantitate CD3+ cells. Results Animals receiving alcohol had increased rates of intestinal T‐cell turnover of both CD4+ and CD8+ T cells as reflected by increased BrdU incorporation. However, absolute numbers of T cells were decreased in intestinal tissues as evidenced by immunohistochemistry for total CD3 expression per mm2 intestinal lamina propria in tissue sections. Combining immunohistochemistry and flow cytometry data showed that the absolute numbers of CD8+ T cells were significantly decreased, whereas absolute numbers of total CD4+ T cells were minimally decreased. Conclusions Collectively, these data indicate that alcohol exposure to the small intestine results in marked loss of CD3+ T cells, accompanied by marked increases in CD4+ and CD8+ T‐cell proliferation and turnover, which we speculate is an attempt to maintain stable numbers of T cells in tissues. This suggests that alcohol results in accelerated T‐cell turnover in the gut, which may contribute to premature T‐cell senescence. Further, these data indicate that chronic alcohol administration results in increased levels of HIV target cells (proliferating CD4+ T cells) that may support higher levels of HIV replication in intestinal tissues.